2016
DOI: 10.3847/0004-637x/827/1/29
|View full text |Cite
|
Sign up to set email alerts
|

RE-EVALUATION OF THE16O(N,γ)17O CROSS SECTION AT ASTROPHYSICAL ENERGIES AND ITS ROLE AS A NEUTRON POISON IN THEs-PROCESS

Abstract: The doubly-magic nucleus 16 O has a small neutron capture cross section of just a few tens of microbarn in the astrophysical energy region. Despite of this, 16 O plays an important role as neutron poison in the astrophysical slow neutron capture (s) process due to its high abundance. We present in this paper a re-evaluation of the available experimental data for 16 O(n, γ) 17 O and derive a new recommendation for the Maxwellian-averaged cross sections (MACS) between kT = 5−100 keV. Our new recommendations are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…As usual, s-wave capture decreases with energy by roughly 1/ √ E, whereas p-wave capture increases with √ E. A transition from the 1/ √ E to the √ E behavior is found at several tens of keV. This is a typical result for light nuclei at the upper end of the p-shell like 12 C [21] and in the sd-shell (e.g., 16 O [22,23] and 26 Mg [9]). Important ingredients of the DC calculations like wave functions and overlaps are further illustrated in Fig.…”
Section: Resultsmentioning
confidence: 57%
“…As usual, s-wave capture decreases with energy by roughly 1/ √ E, whereas p-wave capture increases with √ E. A transition from the 1/ √ E to the √ E behavior is found at several tens of keV. This is a typical result for light nuclei at the upper end of the p-shell like 12 C [21] and in the sd-shell (e.g., 16 O [22,23] and 26 Mg [9]). Important ingredients of the DC calculations like wave functions and overlaps are further illustrated in Fig.…”
Section: Resultsmentioning
confidence: 57%
“…16 O may be one of the candidates due to its high abundance and large reaction rate of neutron capture process. It has been shown that the difference of the 16 O(n, γ) 17 O rates apparently influence the weak s-process in massive stars [1], which trigger us to study the properties of 16 O(n, γ) 17 O, especially for its cross section.…”
Section: Introductionmentioning
confidence: 99%
“…Lighter elements with high abundances and/or high neutron capture cross sections compete with the s-process nucleosynthesis of heavier elements by reducing the availability of neutrons. They can act either as "neutron absorbers," when the neutron is recycled in subsequent reaction steps [e.g., 16 O(n, γ ) 17 O(α, n) 20 Ne] or as "neutron poisons"' when the neutron is completely lost for the s-process nucleosynthesis [e.g., 14 N(n, p) 14 C or 25 Mg(n, γ ) 26 Mg] [3]. Hence, these neutron poisons reduce the efficiency of the s process.…”
Section: Introductionmentioning
confidence: 99%